2005
DOI: 10.1007/s10886-005-3543-y
|View full text |Cite
|
Sign up to set email alerts
|

Do Naïve Ruminants Degrade Alkaloids in the Rumen?

Abstract: Three different methods for the culture of rumen microorganisms (Hungate's technique, the Hohenheim in vitro gas production method, and the semicontinuous rumen simulation technique) were employed to study the influence of various alkaloids (sparteine, lupanine, cytisine, atropine, quinidine, lobeline, harmaline, arecoline, nicotine, caffeine, pilocarpine, gramine, senecionine, and monocrotaline) on rumen microorganisms. Rumen micro-organisms from naive ruminants (sheep, cattle) that had not been exposed to th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
9
0
1

Year Published

2010
2010
2019
2019

Publication Types

Select...
4
3
1

Relationship

2
6

Authors

Journals

citations
Cited by 20 publications
(12 citation statements)
references
References 57 publications
2
9
0
1
Order By: Relevance
“…It could be hypothesised that horse dung may contain more undigested chemical or mechanical defences of plants. The foregut fermentation of ruminants may allow them to destroy numerous secondary metabolites during digestion (Aguiar and Wink, 2005). These olfactory tests confirmed the trophic preferences of A. constans observed during field trapping experiments, in which adults of this species were collected in much greater abundance in pitfall traps baited with cattle or sheep dung than in traps baited with horse or deer dung (Dormont et al, 2004;Dormont et al, 2007).…”
Section: Discussionsupporting
confidence: 77%
“…It could be hypothesised that horse dung may contain more undigested chemical or mechanical defences of plants. The foregut fermentation of ruminants may allow them to destroy numerous secondary metabolites during digestion (Aguiar and Wink, 2005). These olfactory tests confirmed the trophic preferences of A. constans observed during field trapping experiments, in which adults of this species were collected in much greater abundance in pitfall traps baited with cattle or sheep dung than in traps baited with horse or deer dung (Dormont et al, 2004;Dormont et al, 2007).…”
Section: Discussionsupporting
confidence: 77%
“…The potential role of the bacteria and other micro-organisms in the rumen or intestines 529 should not be ignored (Mattocks 1971;Aguiar and Wink 2005). Lanigan (1970) showed that 530 and subsequently l-goreensine and 7-hydroxy-1-methylpyrrolizidin.…”
Section: Relevance Of the Data For Other Plant Species 509mentioning
confidence: 99%
“…A detoxification of defence chemicals by rumen or gut microbes has also been discussed. Experiments with QAs suggest that they are not degraded by rumen microorganisms (Aguiar and Wink, 2005b). A short intestinal transition time or the ingestion of clay, which can adsorb dietary toxins (geophagy), can be additional mechanisms that have been observed in some herbivores.…”
Section: Animal Responses: Detoxification Mechanisms and Adaptationsmentioning
confidence: 99%